Potential impact of climate change on drought-tolerant maize varieties and nitrogen fertilization in Nigeria savannas: a decision support tool (DST) analysis - Beah, A.A.; Akinseye, F.M.; Kamara, A.; Jibrin, J.M.; Tofa, A. (2025)
Purpose – Nitrogen fertilization is a crucial factor in sustainable agriculture practices because it enhances the resilience of maize crops to climate change. This study aims to quantify location-specific adaptation measures to climate change using drought-tolerant maize varieties and N fertilization in the savannas of Nigeria using the Agricultural Production Systems Simulator (APSIM) model. Design/methodology/approach – The calibrated APSIM-maize module was validated using an independent dataset from field experiments conducted under different N fertilization levels within savanna agroecological zones (AEZs). The impacts of climate change were assessed under low and high emissions representative concentration pathways (RCPs), 4.5 and 8.5 W m2 scenarios, for the near-term (2010–2039) and mid-century (2040–2069).